ETHNOBOTANICAL INVESTIGATION OF INDIGENOUS PLANTS USED IN THE MANAGEMENT OF SOME INFANT ILLNESSES IN IBADAN, SOUTH-WESTERN NIGERIA - Aworinde, David Olaniran; Erinoso, Sakiru Morenikeji (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Ethnobotanical information on indigenous plants used in the management of infant illnesses was sourced from Bode herbal market in Ibadan South-western Nigeria to preserve indigenous knowledge of medicinal plants, and demonstrate the role of traditional medicine as complementary healthcare system. Methods: Information was gathered using periodic open-ended questionnaire and personal interview. The respondents were randomly selected and consist, fifteen (15) women - herb sellers (of between 25-50, age range) who prescribed workable recipes used in the management of scalp infections, abscess, convulsion and cold shivers. The recipes documented are enumerated and served as groundbreaking preparations in infant diseases’ management. Results: The survey yielded 48 plant species belonging to 31 plant families. The family Fabaceae has the highest number of species followed by Combretaceae, Meliaceae, Euphorbiaceae. The leaves and roots constituted the frequency of plant parts used; while the stem has the least frequency. The methods of preparation purposefully cited were decoction, infusion, and soap; others include steeping in cold water and cream whereas the solvent of choice was water. A particular brand of bottle water was preferable for herbal preparation. Other ingredients cited include soft traditional black soap, sulphur, Shea butter, antimony/black lead ore, and local sponge. Method of administration and dosage involves diluting extracts from infusion or decoction in higher parts of water – to be drunk, as well as for bath. Conclusion and Application of Results: The study documented indigenous knowledge of plants used in the management of infants’ ailments. Results showed that herbal medicines have played and will continue to play significant roles as alternative or complementary healthcare delivery system. There is need for the sensitization of indigenous people on the conservation of plant resources especially in cases where the root (part) features in prescriptions. A regulatory measure for herbal practitioners as well as public enlightenment is recommended to help sustain and increase the awareness in herbal therapy to different audience. Again, the isolation and identification of active compounds as well as evaluative toxicity test could reveal and confirm indigenous claims by assurring safety in administration.